2011
DOI: 10.1177/0148607111428452
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Lock Therapy in Reducing Catheter‐Related Bloodstream Infections in Adult Home Parenteral Nutrition Patients

Abstract: This study supports the efficacy and safety of ELT in reducing CRBSI-related admissions in HPN patients and potentially helps reduce the burden of CRBSI-related healthcare costs. This novel technique shows great promise as a standard prophylaxis for CRBSI in HPN patients and must be incorporated in routine practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 31 publications
(42 reference statements)
0
68
0
Order By: Relevance
“…23 Various definitions were used to calculate infection rates. Researchers who focused on device-associated infections often reported infection rates as the number of infections per 1,000 device days 12-14,16,21,25,26,28-32,35,38 ; with some exceptions such as the number of infections per catheter year, 15,24,33 the number of infections per 100 catheter insertions, 37 the number of infections per 1,000 HPN days, 30 and the number of infections during the 31-month study period. 34 Researchers who studied various types of infections (eg, sepsis, urinary tract infection, respiratory infections, and skin infections) usually reported the proportion of infected patients out of the total number of patients.…”
Section: Resultsmentioning
confidence: 99%
“…23 Various definitions were used to calculate infection rates. Researchers who focused on device-associated infections often reported infection rates as the number of infections per 1,000 device days 12-14,16,21,25,26,28-32,35,38 ; with some exceptions such as the number of infections per catheter year, 15,24,33 the number of infections per 100 catheter insertions, 37 the number of infections per 1,000 HPN days, 30 and the number of infections during the 31-month study period. 34 Researchers who studied various types of infections (eg, sepsis, urinary tract infection, respiratory infections, and skin infections) usually reported the proportion of infected patients out of the total number of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a randomized trial in adult oncology patients found that 70 % ethanol used for 2 h daily decreased the infection rate from 3.1 to 0.6 per 1,000 catheter days. More recent studies in adult home PN patients and hemodialysis patients have found similar results with reductions in catheter infection rates (Broom et al 2012;John et al 2012). …”
Section: Clinical Utility Of Ethanol Locksmentioning
confidence: 69%
“…Trials in the adult population have included patients with long-term central venous catheters, such as dialysis, oncology, and PN patients, and have shown variable results. [5][6][7][8] The goal of this study was to further evaluate benefits of adding prophylactic ELT to all patients with silicone-based tunneled catheters in adult patients on home PN for an advanced form of intestinal failure (type 2 or type 3) as defined by the European Society for Clinical Nutrition and Metabolism (ESPEN). 9 The primary outcomes evaluated were the rates of CLABSI and resulting hospitalizations in patients before and after the initiation of the ELT protocol.…”
Section: Role Of Ethanol Locks In Reducing Bloodstream Infections In mentioning
confidence: 99%